1986
DOI: 10.1126/science.234.4774.340
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Electronic Materials and Devices

Abstract: Electronic materials and devices corrode in the same ways as automobiles, bridges, and pipelines, but their typically small dimensions make them orders of magnitude more susceptible to corrosion failure. As elsewhere, the corrosion involves interactions with the environment. Under control, these interactions can be put to use, as in the formation of protective and functional oxide films for superconducting devices. Otherwise, they cause damage, as in the electrolytic dissolution of conductors, even gold, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 19 publications
0
73
0
Order By: Relevance
“…It is reported that even small amounts of weight loss, of the order of nanograms or less, can cause problems and ultimately lead to device failure. 1 Electrochemical migration (ECM) is a common reliability problem which is related to failure encountered in the electronics industry. It is dened as a process by which a metal, in contact with insulating materials and under an electrical potential, is removed ionically from its initial location and is redeposited at other location.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that even small amounts of weight loss, of the order of nanograms or less, can cause problems and ultimately lead to device failure. 1 Electrochemical migration (ECM) is a common reliability problem which is related to failure encountered in the electronics industry. It is dened as a process by which a metal, in contact with insulating materials and under an electrical potential, is removed ionically from its initial location and is redeposited at other location.…”
Section: Introductionmentioning
confidence: 99%
“…Fine particles (<2 mm in diameter) are more difficult to remove by filtration and hence may be found in significant concentrations in indoor environments, even those with good air-handling systems. These particles, which typically result from combustion processes, are likely to contain a high proportion of water-soluble ionic compounds that are more corrosive than the natural materials [1,[3][4][5]. The most common ions found in these particles, NH 4 þ and SO 4 2 À , are typically present in roughly equal molar proportions [1].…”
Section: B Environment and Contaminationmentioning
confidence: 99%
“…Chloride ions present in many environments are very aggressive agent which can cause extensive corrosion of many materials [2,[5][6][7]. Chloride containing corrosion products are then very often detected on iron and copper objects [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…metals, alloys, concrete, glasses) that result from reaction with the corrosive environment [1]. The corrosion process depends on various factors, such as environment, pH, temperature, presence of the oxygen or aggressive ions in aqueous solution [1][2][3].…”
Section: Introductionmentioning
confidence: 99%